Managing housing needs in post conflict housing reconstruction in Sri Lanka: gaps verses recommendations - Seneviratne, Krisanthi; Amaratunga, Dilanthi; Haigh, Richard (International Journal of Strategic Property Management, 2016)
Addressing housing needs in post conflict housing reconstruction leads to successful housing reconstruction. As part of a study of investigating how the housing needs can be effectively addressed in post conflict housing reconstruction, this paper identifies the gaps in managing housing needs in post conflict housing reconstruction within the context of Sri Lanka and presents the recommendations to minimise such gaps. Data was collected through un-structured interviews conducted with 37 participants, comprising policy makers, practitioners, academics and beneficiaries who engaged in post conflict housing reconstruction in Sri Lanka. Gaps were mainly found in conflict sensitivity, measures related to physical housing, performance of implementing agencies, policy and practice issues. On the job training, application of ‘do no harm’ principles, enhanced beneficiary participation, enhanced accountability, effective monitoring, enhanced knowledge sharing, adequate drinking water facilities, irrigation development and initiatives for material manufacturing were suggested as recommendations to minimise these gaps. Identification of gaps in managing housing needs in post conflict housing reconstruction and recommendations to minimise them inform policy makers to address the housing needs effectively through incorporating these aspects into the related policies. This in turn enhances the sustainability in housing development after conflicts.